What Are the Minimal and Substantial Improvements in the HOOS and KOOS and JR Versions After Total Joint Replacement?. Issue 12 (December 2018) - Lyman, Stephen; Lee, Yuo-Yu; McLawhorn, Alexander S.; Islam, Wasif; MacLean, Catherine H.
Abstract: Background: Patient-reported outcome measures (PROMs) are a gold standard for measuring therapeutic outcomes in research. Extending their use to inform clinical care decisions, determine the appropriateness of therapeutic choices, and assess healthcare quality is attractive but will require our professional community to establish valid estimates of minimal and substantial clinical improvements. Questions/purposes: The purposes of this study were (1) to assess the validity of estimates for the minimal clinically important difference (MCID) calculated using distribution- and anchor-based methods by determining whether they exceed the minimal detectable change (MDC) for the Hip Disability and Osteoarthritis Outcome Score (HOOS) and the Knee Injury and Osteoarthritis Outcome Score (KOOS) domains, the HOOS, joint replacement (JR) and the KOOS, JR among patients who underwent THA or TKA; (2) to determine substantial clinical benefit thresholds for the HOOS and KOOS domains, the HOOS, JR, and the KOOS, JR among patients who underwent THA or TKA; and (3) to assess the proportions of patients who underwent THA or TKA who achieved an MCID for the HOOS and KOOS domains, HOOS, JR, and KOOS, JR based on distribution-based and anchor-based methods as well as the percentages of patients who achieved substantial clinical benefit using the anchor-based method. Methods: Medicare patients enrolled in our institutional joint replacement registry who subsequently underwent THA (n = 2323) or TKA (n = 2630) between 2007 and 2012 completed HOOS or KOOS preoperatively and 2 years postoperatively. Short-form joint replacement (JR) versions of each PROM were derived from the full PROMs. Of all eligible patients, 78% (3161 of 4080) of THAs and 74% of TKAs (3815 of 5156) consented to join the registry and completed a baseline survey, 88% (2796 of 3161) of THAs and 85% (3230 of 3815) of TKAs were eligible for followup survey administration, and 83% of THAs (2323 of 2796) and 81% (2630 of 3230) of TKAs returned 2-year surveys. For each HOOS domain, KOOS domain, HOOS, JR, and KOOS, JR, we calculated the calibration variation of the instrument (MDC) with confidence intervals (CIs) reflecting 80% (MDC80), 90% (MDC90), and 95% (MDC95) certainty; we calculated the smallest difference joint health patients might detect (MCID) using distribution- and anchor-based approaches and the difference that can be considered a large improvement in joint health (substantial clinical benefit) using an anchor-based approach. Results: Patients undergoing THA were 57% female with a mean (± SD) age of 73 ± 6 years, whereas patients undergoing TKA were 63% female with a mean age of 74 ± 6 years. Depending on the CI chosen for the MDC, values ranged from 7 to 16 for the HOOS and KOOS domains and the JRs. The MCIDs ranged from 6 to 9 for the distribution-based approach and 7 to 36 for the anchor-based approach. All HOOS and KOOS domains and all JR scores are scores from 0 (worst joint health) to 100 (best joint health). The MCIDs calculated using the distribution-based approach were not valid, because they were lower than the MDC for all HOOS/KOOS domains and both JRs at every confidence level. The anchor-based receiver operating characteristic approach, on the other hand, resulted in MCIDs exceeding MDC80 for seven of eight HOOS/KOOS domains and MDC95 for both JR scores. For all domains and JR versions, substantial clinical benefits ranged from 15 to 36, exceeding MDC95 in all domains and JR scores. Across HOOS and KOOS domains as well as the JR, the proportion of patients undergoing THA who achieved an MCID ranged from 77% to 95% with the distribution-based method and from 67% to 96% using the anchor-based method. The proportion achieving substantial clinical benefit ranged from 67% to 85%. Conclusions: The MDC and MCID differ greatly based on assumptions and methods used. The MCID anchor-based approach had superior construct and face validity compared with the MCID distribution-based approach, which never exceeded even small MDCs. Achieving consensus about standard definitions of meaningful improvement will be necessary to maximize utility of these PROMs to inform clinical care or performance measurement. Level of Evidence: Level III, diagnostic study.